1996
DOI: 10.1212/wnl.47.2.425
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis and anti-inflammatory agents as possible protective factors for Alzheimer's disease

Abstract: Alzheimer's disease (AD) lesions are characterized by the presence of numerous inflammatory proteins. This has led to the hypothesis that brain inflammation is a cause of neuronal injury in AD and that anti-inflammatory drugs may act as protective agents. Seventeen epidemiologic studies from nine different countries have now been published in which arthritis, a major indication for the use of anti-inflammatory drugs, or anti-inflammatory drugs themselves have been considered as risk factors for AD. Both factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
674
1
16

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,274 publications
(708 citation statements)
references
References 14 publications
17
674
1
16
Order By: Relevance
“…Earlier, we had reported that sustained use of NSAID might contribute to the development of renal cell carcinoma, and that such exposure might explain approximately 20% of the cases diagnosed in Los Angeles County (Gago-Dominguez et al, 1999). On the other hand, there is growing evidence that NSAID use protects against colorectal cancer, Alzheimer's disease and ischaemic heart disease (Steering Committee of the Physicians' Health Study Research Group, 1989;Giovannucci et al, 1995;McGeer et al, 1996). This study suggests that NSAID use also may protect against another relatively common cancer in the USA as well as worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we had reported that sustained use of NSAID might contribute to the development of renal cell carcinoma, and that such exposure might explain approximately 20% of the cases diagnosed in Los Angeles County (Gago-Dominguez et al, 1999). On the other hand, there is growing evidence that NSAID use protects against colorectal cancer, Alzheimer's disease and ischaemic heart disease (Steering Committee of the Physicians' Health Study Research Group, 1989;Giovannucci et al, 1995;McGeer et al, 1996). This study suggests that NSAID use also may protect against another relatively common cancer in the USA as well as worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that inflammatory processes play an active role in AD; epidemiological studies reported that the use of nonsteroidal anti-inflammatory drugs is associated with marked reduction in the risk of AD ( [106,154,156,219,225]). Following this initial observation, additional reports were published that witnessed the involvement of neuroinflammation in AD pathogenesis and progression.…”
Section: Alzheimer's Disease and Neuroinflammationmentioning
confidence: 99%
“…Neuropathological and epidemiological data suggest that inflammatory mediators and immune mechanisms may play a role in the pathogenesis of Alzheimer's disease (AD) (McGeer et al, 1996;Cagnin et al, 2001;Ho et al, 2001;in 't Veld et al, 2002;Etminan et al, 2003). It has been proposed that these effects may be mediated via the COX-2 enzyme (Pasinetti, 2001).…”
Section: Introductionmentioning
confidence: 99%